2015
DOI: 10.1001/jamaoncol.2015.0917
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Intraoperative Molecular Characterization of Glioma

Abstract: IMPORTANCE Conclusive intraoperative pathologic confirmation of diffuse infiltrative glioma guides the decision to pursue definitive neurosurgical resection. Establishing the intraoperative diagnosis by histologic analysis can be difficult in low-cellularity infiltrative gliomas. Therefore, we developed a rapid and sensitive genotyping assay to detect somatic single-nucleotide variants in the telomerase reverse transcriptase (TERT) promoter and isocitrate dehydrogenase 1 (IDH1). OBSERVATIONS This assay was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 15 publications
(21 reference statements)
0
55
0
Order By: Relevance
“…A mutation-specific telomerase promoter PCR quantifies tumor purity Although allele-specific PCR has been used qualitatively for genotyping glioma (25), it can also be performed quantitatively for allele frequency estimation (26). To sensitively detect telomerase promoter mutations, we established an allele-specific quantitative real-time PCR (qAS-PCR) assay for the two commonly observed hotspot mutations (chr5:1,295,228G>A and chr5:1,295,250G>A) in the TERT promoter (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A mutation-specific telomerase promoter PCR quantifies tumor purity Although allele-specific PCR has been used qualitatively for genotyping glioma (25), it can also be performed quantitatively for allele frequency estimation (26). To sensitively detect telomerase promoter mutations, we established an allele-specific quantitative real-time PCR (qAS-PCR) assay for the two commonly observed hotspot mutations (chr5:1,295,228G>A and chr5:1,295,250G>A) in the TERT promoter (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, specimens may be small and not representative, hampering correct diagnosis or even necessitating multiple surgical samplings to clarify final pathologic diagnosis. In addition, the surgical intervention strategy and assessment of the surgical risk-benefit balance depend on the glioma subtype (1, [9][10][11]. This implies that an intraoperative histologic diagnosis may be required, possibly delaying the surgical procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic testing remains timeconsuming [reporting of isocitrate dehydrogenase (IDH) mutation status, a prognostic marker, can take weeks], creating delay in pathologic diagnosis and rendering treatment. However, recently, Shankar et al (17) reported a genotyping method for IDH and telomerase reverse transcriptase mutations, with results available in 60 min.…”
mentioning
confidence: 99%